Volland: A Flint Hills Story - Greg Hoots (Symphony in the Flint Hills, 2011)
After the Kansas Territory was created in 1854, settlers from the East eagerly anticipated the opportunity to obtain the new land. On May 30, 1867, Franz Fritz acquired a land patent from the United States government giving him property at what is today Volland. On the same day he acquired the property, Fritz sold the land to Henry and Barbara Volland, who were among the numerous German immigrants that had settled Washington Township just west of Alma.
Keywords: Volland; Flint Hills; settlers; land; German; Immigrants; Washington Township; Alma; Wabunsee County; Manhattan; Burlingame; Rock Island; Grafton; stockyards; depot; store; railroad; school; historic; lost town